2016
DOI: 10.1515/prolas-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Contrast-Enhanced Ultrasound Evaluation of Malignant and Benign Solitary Thyroid Nodules

Abstract: # Corresponding author Contributed by Jânis GardovskisThe aim of the study was to investigate the diagnostic value of contrast-enhanced ultrasound (CEUS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The innovations in ultrasonography include contrast-enhanced ultrasonography, elastography and superb microvascular imaging [1,38,39].…”
Section: Radiological Evaluation Of a Thyroid Nodulementioning
confidence: 99%
“…The innovations in ultrasonography include contrast-enhanced ultrasonography, elastography and superb microvascular imaging [1,38,39].…”
Section: Radiological Evaluation Of a Thyroid Nodulementioning
confidence: 99%
“…In a follow up study, Agha et al showed that CEUS had a sensitivity of 95.9% for the detection of pathological parathyroid glands in comparison to 60.8% for (99m) Technetium-sestamibi scintigraphy. Sensitivity of CEUS in patients with negative scintigraphy was 96.3% [100,101].…”
Section: Color Doppler Imagingmentioning
confidence: 99%